Long Term Energy Strategies and Policies: Challenges. (2015) - Ţărean, Cristina
Abstract: Energy is at the top of the global agenda today so the article proposes an overview and identification of the major challenges brought by the development of energy strategies and policies. Romania's energy strategy requires an update given that in the existing one was not well estimated the evolution in energy field and should have been correlated with different sector from the economy. The aim of this paper is to offer an overview and a better understanding about the challenges over energy sector and about general steps for organizing a project for developing a new strategy.